2019
DOI: 10.1101/560482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Omentum-inspired 3D PEG Hydrogel for Identifying ECM-drivers of Drug Resistant Ovarian Cancer

Abstract: Ovarian cancer (OvCa) is a challenging disease to treat due to poor screening techniques and late diagnosis. There is an urgent need for additional therapy options, as patients recur in 70% of cases. The limited availability of clinical treatment options could be a result of poor predictions in early stage drug screens on standard tissue culture polystyrene (TCPS). TCPS does not capture the mechanical and biochemical cues that cells experience in vivo, which can impact how cells will respond to a drug. Therefo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…2G). Previous studies have shown that spheroid formation from single cancer cells occurs within ~2 weeks (9,12,37), indicating that the PA-VH/KN hydrogels are sufficiently stable to support spheroid formation. The discrepancy between the quantified weight loss and the unchanged hydrogel structure may be attributed to swelling effects of the hydrogels, with >90% water content (22).…”
Section: Hydrogel Stability Characterizationmentioning
confidence: 98%
“…2G). Previous studies have shown that spheroid formation from single cancer cells occurs within ~2 weeks (9,12,37), indicating that the PA-VH/KN hydrogels are sufficiently stable to support spheroid formation. The discrepancy between the quantified weight loss and the unchanged hydrogel structure may be attributed to swelling effects of the hydrogels, with >90% water content (22).…”
Section: Hydrogel Stability Characterizationmentioning
confidence: 98%
“…The disparity in performance between the training and testing data sets may be related to differences in the expression patterns in different tissue types, or batch effects. IC 50 measurements for the same cell line and drug are known to vary significantly between studies, especially when the cell line is drug insensitive, 92 which may contribute to the poor correlation between results of both data sets.…”
Section: Discussionmentioning
confidence: 99%
“…The disparity in performance between the training and testing data sets may be related to differences in the expression patterns in different tissue types, or batch effects. IC 50 measurements for the same cell line and drug are known to vary significantly between studies, especially when the cell line is drug insensitive, 92 which may contribute to the poor correlation between results of both datasets.…”
Section: Discussionmentioning
confidence: 99%